The Career Indecision Profile: Measurement Equivalence in the United States and South Korea. (May 2015) - Abrams, Matthew D.; Lee, In Heok; Brown, Steven D.; Carr, Andrea
This study tested for the measurement equivalence of a four-factor measure of career indecision (Career Indecision Profile-65; CIP-65) in U.S. and South Korean samples. The study was conducted in three phases. In the first phase, we tested the measurement equivalence of the CIP-65 with samples of participants from the United States ( n = 488) and South Korea ( n = 574). Finding a lack of evidence for configural invariance, we randomly split the South Korean sample to establish a version of the CIP-65 that would better fit the South Korean data. First, we conducted an exploratory factor analysis on data collected from 200 participants. A five-factor model of career indecision emerged that contrasted with our four-factor model. Second, we tested the five-factor structure by conducting a confirmatory factor analysis on data collected from 374 participants. The results revealed that the five-factor model fit the data well. Implications from these findings for counseling and future research are discussed.